If we have a plane vector n = [a, b, c, d] which describes a plane then for any point p = [x, y, z, 1] in that plane the follow equation holds:html
nt p = ax + by + cz + d = 0 app
If for a point p on the plane, we apply an invertible transformation R to get the transformed point p1, then the plane vector n1 of the transformed plane is given by applying a corresponding transformation Q to the original plane vector n where Q is unknown. post
p1 = R p
n1 = Q n orm
n1t p1 = 0 htm
Begin by substituting for n1 and p1:(Q n)t (R p) = 0
nt Qt R p = 0 blog
Qt R = I
Qt = R-1
Q = (R-1)t get
n1 = Q n = (R-1)t n it